2016
DOI: 10.1159/000438651
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Type I Receptor Kinase Inhibitor EW-7197 Suppresses Cholestatic Liver Fibrosis by Inhibiting HIF1α-Induced Epithelial Mesenchymal Transition

Abstract: Background/Aims: Hypoxia is an environmental factor that aggravates liver fibrosis. HIF1α activates hepatic stellate cells (HSCs) and increases transforming growth factor-β (TGF-β) signaling and the epithelial mesenchymal transition (EMT), accelerating the progression of fibrosis. We evaluated the anti-fibrotic therapeutic potential of a small-molecule inhibitor of TGF-β type I receptor kinase, EW-7197, on HIF1α-derived TGF-β signaling in cholestatic liver fibrosis. Methods: We used a bile duct ligation (BDL)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 65 publications
3
37
0
Order By: Relevance
“…Furthermore, Smad3 is present at high levels in fibrotic tissues [41], and up-regulated Smad2 expression compensates for Smad3 [42] [43]. We found that the mRNA expressions of Smad2 and Smad3 were elevated and the amount of phosphorylated Smad2 was up-regulated conspicuously.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, Smad3 is present at high levels in fibrotic tissues [41], and up-regulated Smad2 expression compensates for Smad3 [42] [43]. We found that the mRNA expressions of Smad2 and Smad3 were elevated and the amount of phosphorylated Smad2 was up-regulated conspicuously.…”
Section: Discussionmentioning
confidence: 95%
“…Cholestasis accompanied with excessive accumulation of bile acids in hepatic tissue can result in cholestatic hepatic fibrosis and cirrhosis [2,3]. LCA is a monohydroxy hydrophobic bile acid produced in the gut by bacterial reduction of chenodeoxycholic acid [20].…”
Section: Discussionmentioning
confidence: 99%
“…An accumulation of highly toxic bile acids in the hepatocytes leads to cytotoxicity and cholestatic liver injury. Persistent cholestatic liver damage results in marked inflammatory reactions that can eventually lead to the activation and proliferation of hepatic stellate cells, overproduction of matrix metalloproteinases, synthesis of extracellular matrix, liver fibrosis, cirrhosis, and even death [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic stellate cells (HSCs) are the main source of the ECM, and their activation is a pivotal event in hepatic fibrogenesis [3, 4]. Thus, enhancing the apoptosis of activated HSCs is of great importance to the treatment of liver fibrosis [5].…”
Section: Introductionmentioning
confidence: 99%